The Importance of Knowledge Management in Higher Education Organizations - Tawfiq Seraa; Bachir Ameur (Dirassat Journal Economic Issue, 2019)
This paper presents a framework for highlighting knowledge management importance in higher education. The framework has a descriptive nature and aims to be useful to characterize knowledge management implementations, facilitating the identification and selection of appropriate tools in higher education organizations according to their needs. Knowledge is recognized as one of the most important assets of higher education organizations. Managing knowledge has grown to be vital for an organization’s success.